52. KNOWLEDGE AND PRACTICES ON REPRODUCTIVE HEALTH OF STUDENTS OF THANG LONG HIGH SCHOOL, NGO QUYEN, HAI PHONG IN 2025 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objective: Assessment of knowledge, practice and some related factors on adolescent reproductive health care of students at Thang Long High School, Ngo Quyen, Hai Phong in 2025.Methods: Analytical cross-sectional study. The study collected information from 420 students in 3 high school blocks of Thang Long High School, Ngo Quyen, Hai Phong. Data was entered using Epidata 3.1 software and analyzed using SPSS 26.0 statistical software.Results: The rate of students with knowledge of the concept of adolescent reproductive health is 65.7%, knowledge of puberty is 51.0%, knowledge of sexual safety is 51.4%, knowledge of contraception is 42.4%, knowledge of pregnancy is 40.2%, knowledge of sexually transmitted diseases is 58.6%. The rate of practice in personal hygiene to ensure reproductive health among students is 76.4%, among female students is 81.6%, among male students is 71.4%. The rate of practice in students on handling signs of genital diseases is 71.5%, among female students is 73.6%, among male students is 69.5%.Conclusion: General knowledge of adolescent reproductive health of students reached 52.1%, General practice of adolescent reproductive health of students reached 69.2%. There were factors related to academic performance and grade level with knowledge about adolescent reproductive health. Adolescent reproductive health care practices were related to students attending educational sessions, academic performance and general knowledge about adolescent reproductive health (p
Keywords: Adolescents; Knowledge; practices; adolescent reproductive health.